2017
DOI: 10.1186/s40634-017-0110-8
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular arthrofibrosis of the knee alters patellofemoral contact biomechanics

Abstract: Background: Arthrofibrosis in the suprapatellar pouch and anterior interval can develop after knee injury or surgery, resulting in anterior knee pain. These adhesions have not been biomechanically characterized. Methods: The biomechanical effects of adhesions in the suprapatellar pouch and anterior interval during simulated quadriceps muscle contraction from 0 to 90°of knee flexion were assessed. Adhesions of the suprapatellar pouch and anterior interval were hypothesized to alter the patellofemoral contact bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…This investigation has demonstrated that arthrofibrosis of the knee decreased the range of patellar inferior shift and flexion during 15°to 75°of knee flexion with a large effect. These findings are consistent with the in-vitro study results obtained by Mikula et al, 18 which showed that arthrofibrosis in the suprapatellar pouch resulted in decreases in patellar inferior shift and flexion. In the knee, arthrofibrosis involves the patellofemoral compartment, occurring in the suprapatellar pouch, the infrapatellar fat pad, and the anterior interval, which might restrict the patella from shifting inferiorly effectively during knee flexion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This investigation has demonstrated that arthrofibrosis of the knee decreased the range of patellar inferior shift and flexion during 15°to 75°of knee flexion with a large effect. These findings are consistent with the in-vitro study results obtained by Mikula et al, 18 which showed that arthrofibrosis in the suprapatellar pouch resulted in decreases in patellar inferior shift and flexion. In the knee, arthrofibrosis involves the patellofemoral compartment, occurring in the suprapatellar pouch, the infrapatellar fat pad, and the anterior interval, which might restrict the patella from shifting inferiorly effectively during knee flexion.…”
Section: Discussionsupporting
confidence: 93%
“…2 The decreased patellar tilt in the affected knee could be responsible for flexion contracture associated with arthrofibrosis after ACL reconstruction. 18 Because of the high congruency of the PFJ, an alteration in patellar tracking would be expected to lead to persistent knee symptoms and changes in patellofemoral contact characteristics in individuals with arthrofibrosis after ACL reconstruction. 21 Indeed, other investigators found that the more superiorly shifted position of the patella indicates decreased quadricepspatellar tendon angle and increased patellofemoral contact force, resulting in anterior knee pain and degeneration of patellofemoral cartilage in the long term.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, scarring of the anterior interval can cause patella baja and may lead to patellofemoral arthritis. 5 The rate of patella baja after autogenous patellar tendon ACL reconstruction has been reported to be as high as 76% in 1 case series. 8 Therefore, we believe anterior interval scarring after ACL reconstruction is an under-recognized condition.…”
Section: Discussionmentioning
confidence: 99%
“…A recent biomechanical analysis showed anterior interval scarring significantly increased patellofemoral contact forces at all flexion angles tested. 5 The goal of this paper is to describe the technique for anterior interval release (AIR) of the knee.…”
mentioning
confidence: 99%
“…The minimal clinically important difference on the Kujala scale was 10, and the patient's Kujala scale improved by 20 points, which is a clinically meaningful improvement [ 11 ]. Previous studies have reported that irritation of the IPFP is a potential source of AKP [ 12 ], that the histopathological changes in IPFP are associated with patellofemoral disorders [ 13 - 15 ], and that pain during stair descent is characteristic of patellofemoral disorders [ 15 - 19 ].…”
Section: Discussionmentioning
confidence: 99%